2023
DOI: 10.3390/microorganisms11041031
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Airborne Mycobiota Surveillance in High-Risk Hospital Environment

Abstract: (1) Background: The primary aim of the presented study was to assess the prevalence of fungi in the indoor air of selected hospital wards, and the additional goal was to evaluate the susceptibility of cultured isolates of Aspergillus fumigatus to triazoles. (2) Methods: Three hematology departments and a hospital for lung diseases were surveyed in 2015 and/or 2019. Air samples were taken with a MicroBio MB1 air sampler on Sabouraud agar. The susceptibility of Aspergillus fumigatus isolates to voriconazole, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…In a study by Alghamdi and collaborators [18], the authors described several species of filamentous fungi and reported the yeasts identified as other fungi. Similarly, Gorzynska et al [19] reported indoor air contamination by yeasts in selected hospital environments. However, the authors failed to identify the species, grouping them only as non-pigmented and pigmented yeasts.…”
Section: Introductionmentioning
confidence: 91%
“…In a study by Alghamdi and collaborators [18], the authors described several species of filamentous fungi and reported the yeasts identified as other fungi. Similarly, Gorzynska et al [19] reported indoor air contamination by yeasts in selected hospital environments. However, the authors failed to identify the species, grouping them only as non-pigmented and pigmented yeasts.…”
Section: Introductionmentioning
confidence: 91%